The Role of Flavonoids in the Osteogenic Differentiation of Mesenchymal Stem Cells - Zhang, Jinli; Liu, Zhihe; Luo, Yang; Li, Xiaojian; Huang, Guowei; Chen, Huan; Li, Aiguo; Qin, Shengnan (Frontiers in Pharmacology, 2022)
Mesenchymal stem cells (MSCs) play an important role in developing bone tissue engineered constructs due to their osteogenic and chondrogenic differentiation potential. MSC-based tissue engineered constructs are generally considered a safe procedure, however, the long-term results obtained up to now are far from satisfactory. The main causes of these therapeutic limitations are inefficient homing, engraftment, and directional differentiation. Flavonoids are a secondary metabolite, widely existed in nature and have many biological activities. For a long time, researchers have confirmed the anti-osteoporosis effect of flavonoids through in vitro cell experiments, animal studies and clinical experimental reports. In recent years the regulatory effects of flavonoids on mesenchymal stem cells (MSCs) differentiation have been received increasingly attention. Recent studies revealed flavonoids possess the ability to modulate self-renewal and differentiation potential of MSCs. In order to facilitate further research on MSCs osteogenic differentiation of flavonoids, we surveyed the literature published on the use of flavonoids in osteogenic differentiation of MSCs, and summarized their pharmacological activities as well as the underlying mechanisms , aimed to explore their promising therapeutic application in the bone tissue engineered constructs and regeneration.